(untitled) (Journal of Mechanical Engineering, 2013)
The present numerical simulation is analyzed the Magnetohydrodynamic natural convection flow andheat transfer along a uniformly heated vertical wavy surface in presence of heat generation/absorption withtemperature dependent variable viscosity. Using the appropriate transformations the governing boundary layerequations are reduced to non-dimensional forms. The resulting nonlinear system of partial differentialequations are mapped into the domain of a vertical flat plate and then solved numerically applying implicitfinite difference method together with Keller-box scheme. The solutions are expressed in terms of the skinfriction coefficient, the rate of heat transfer, the streamlines as well as the isotherms over the whole boundarylayer. The implications of heat generation/absorption parameter (Q) and viscosity parameter (?) on the flowstructure and heat transfer characteristics are investigated in detail while, Prandtl number (Pr), magneticparameter (M) and the amplitude-to-length ratio of the wavy surface (?) are considered fixed. Comparison withpreviously published work is performed and is found to be in good agreement. DOI: http://dx.doi.org/10.3329/jme.v42i1.15944